Summer movement patterns of Arctic lemmings ( Lemmus sibiricus and Dicrostonyx groenlandicus ) - Rodgers, Arthur R. (Canadian Journal of Zoology, 1990)
Several measures of movement based on livetrapping data were used to compare summer movement patterns of Lemmus sibiricus and Dicrostonyx groenlandicus in northern Canada. Distances moved by individuals of both species were greater when populations were intermediate in size than at high or low density. At intermediate density, males of both species moved farther than females. Seasonal movement patterns of the two species were similar. Coincident with reproductive periods in late July and late August, distances moved decreased in both species. Increased movements of both species followed periods of reproductive activity and also occurred at the end of each summer. These latter movements are related to seasonal changes in patterns of habitat use and diet in each species. These results suggest that dispersal is an important determinant of seasonal patterns of population change in both L. sibiricus and D. groenlandicus.